2005
DOI: 10.1007/s00701-005-0645-9
|View full text |Cite
|
Sign up to set email alerts
|

Chiari malformation: CSF flow dynamics in the craniocervical junction and syrinx

Abstract: In ChM, the posterior cervical CSF flow velocity was low, increased minimally after CCJD and, by itself, had limited predictive value. Post-CCJD, an increase of the sum of anterior and posterior cervical CSF flow velocities by more than 20% consistently preceded or coincided with marked headache improvement. After CCJD, the finding that the intrasyringeal CSF pulsatile motion had become absent was an earlier and more sensitive predictor of motor or sensory improvement than a reduction in syrinx's size. SPAMM c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 28 publications
3
28
0
4
Order By: Relevance
“…27 Second, the peak velocities and flow durations reported by us are consistent with results obtained by others using sagittal cine-PC imaging in different Chiari I populations. 13,14,25,26 Finally, long diastolic durations observed by us in patients with Chiari I with CAH with sagittal imaging are consistent with the phenomenon of anterior diastolic CSF flow jets reported in symptomatic patients with Chiari I by Quigley et al 19 by using axial cine-PC imaging. These investigators also observed simultaneous bidirectional flow at the foramen magnum.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…27 Second, the peak velocities and flow durations reported by us are consistent with results obtained by others using sagittal cine-PC imaging in different Chiari I populations. 13,14,25,26 Finally, long diastolic durations observed by us in patients with Chiari I with CAH with sagittal imaging are consistent with the phenomenon of anterior diastolic CSF flow jets reported in symptomatic patients with Chiari I by Quigley et al 19 by using axial cine-PC imaging. These investigators also observed simultaneous bidirectional flow at the foramen magnum.…”
Section: Discussionsupporting
confidence: 85%
“…13,14,25,26 Although it is difficult to directly compare these results with those of our observations (in the absence of the knowledge of how many of their patients had CAH), the reported CSF velocities and durations in these different Chiari I patient populations are similar to our results. 13,14,25,26 Because the differences in CSF flow between patients with Chiari I and healthy subjects has been thoroughly evaluated previously, in this study, we only sought to correlate cine-PC-demonstrated CSF flow abnormalities to the specific subjective symptom of CAH.…”
Section: Discussionsupporting
confidence: 75%
“…[1][2][3][4][5][6][7][8][9][11][12][13][14][15][16][17][18][19][65][66][67]70,71,100,[102][103][104][105][106][107][108][109][110][111][113][114][115][116][117][118][119][120][121][122][123][124][125][126][127][128][129][130][132]…”
Section: General Informationunclassified
“…Combined series, which included both pediatric and adult patients, constituted 61 reports (42%). [5][6][7]9,11,12,[25][26][27]34,37,38,40,43,44,46,47,52,53,55,63,66,67,70,73,74,76,83,87,90,91,94,96,100,102,103,106,110,111,114,115,117,121,126,127,129,130,132,135,[138][139][140]…”
Section: General Informationmentioning
confidence: 99%
“…At present, MRI techniques are being developed to measure CSF pressure gradients noninvasively [14], but these methods are not in standard use and have not been validated. In principle, changes in CSF pressure gradients are related to alterations in impedance to CSF motion, CSF velocities [15][16][17][18][19][20][21][22], neural tissue motion [23][24][25], and craniospinal compliance [26][27][28]. We suspect that alterations in each of these biomechanical parameters could prove useful to quantify the biomechanical environment near the CVJ in CMI.…”
Section: Introductionmentioning
confidence: 99%